Port Efficiency and Supply Chain: Implication for Bangladesh - Sukanta Sen; Md Akramuzzaman Shaikh; Anis Mohammad Tareq; Mohammad Shahedul Islam; Professor Wang Xuefeng (International Journal of Engineering and Management Research, 2020)
Port and supply chains are closely connected to each other as a port is considered as an important node of the global supply chain. Sothe efficiency level of port has an impact on the performance of supply chain operations. Chittagong port is the principal seaport of Bangladesh and it provides a major gateway to the outside world. The cost of doing business is increasing as a result of the inefficiency in the main seaport of the country. In this paper, an effort has been taken to examine the efficiency of Chittagong Port and the causal factors of inefficiency. The impact of inefficiency at Chittagong port on the supply chain of Bangladesh has also been identified. To do this, at first a relationship has been built between port efficiency and supply chain in respect of Bangladesh. Relevant data has been gathered through extensive review of the literature, field surveys, interacting with top management of different business entities such as shipping agency, freight forwarder, logistics companies, exporter, importer as well as Government regulatory and monitoring bodies using both the structured and unstructured questionnaires. The study has revealed that theinefficiency at Chittagong port causes serious consequences on the supply chain of exporter and importer and lead to loss and disruption of trade and ultimately incur extra costs and time. This paper, therefore, recommends a substantial infrastructure improvement to Chittagong port along with other related measures in order to facilitate the supply chain of exporter and importer.